[African Students Club, 1967-1968] (1968)
Photo of the members of the African Students Club from the academic year 1967-1968. The photo was published in the 1968 El Rodeo Yearbook on page 61. Members of the club listed in the yearbook are: Bottom row: Philemon Buhwa, Said A. Said, Festus Soribe, Amos Ngongi. Row 2: Michou Ohin, Shola Onipede, Isaac Oladiji, Sunday Ebojoh. Row 3: Chuka Ezikpe, Ali Dankintafo, Noel Pedanou, Garba Mohammed. Row 4: Hamma Hassane, Adekunle Taiwo, Obediah Butscher, Homevor Augustin, John Buless Gbenedio. Some students are dressed in traditional African garments and others are dressed in business professional attire.